2015
DOI: 10.4103/2277-9175.151302
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the impact of acupuncture and pethidine on reducing labor pain

Abstract: Background:Generally 50 to 70 percent of women suffer from a severe and unbearable pain during their childbirth. Abnormal fetal heart patterns, an increase of caesarian delivery rate, prolonged labor and low APGAR score in newborn are some of adverse effects of labor pain. Disagreement between different studies regarding the efficiency and effectiveness of acupuncture on labor pain led us to do this study.Materials and Methods:This is a clinical trial study. Sampling was done randomly in Esfahan, Shahid Behesh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
14

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 16 publications
0
11
0
14
Order By: Relevance
“…Doğum ağrısının yönetimi için farmakolojik olmayan yöntemler hakkında gebeye bilgi vererek gebe karar verme sürecine dahil edilmelidir. Kadının dahil edilmediği bir süreç kadını bağımlı kılmakta ve sağlık personelini zorlamaktadır (Simkin & Bolding, 2004 tarih aralığında İngilizce "labor pain", "management of labor pain", non-pharmacological methods in management of labor pain" ve "midwife and labor pain" anahtar kelimeleri ile Türkçe "doğum ağrısı", "doğum ağrısının yönetimi", "doğum ağrısının yönetiminde farmakolojik olmayan yöntemler" ve "ebe ve doğum ağrısı" anahtar kelimeleri ile Google Akademik, Science Direct, Wiley Online Library, (Simkin & Bolding, 2004;Fogarty, 2008;Hutton et al, 2009;Derry et al, 2012;Hajiamini et al, 2012;Mollamahmutoğlu ve ark., 2012;Mortazavi et al, 2012;Allameh et al, 2015;Dong et al, 2015;Bolbol-Haghighi et al, 2016;Lakhan et al, 2016;Bonapace et al, 2018;Ranjbaran et al, 2017;Ghiasi et al, 2019;Suarez et al, 2019) Science Direct (Taavoni et al, 2016;Shahoei et al, 2017;Ünalmış 2017;Ali & Hamdia 2018) Cochrane Library (Lawrence et al, 2013;Madden et al, 2016) Researchgate (Askari et al, 2016;Regis et al, (Karami et al, 2007;Hashemi et al, 2012;Barbieri et al, 2013;Ghani, 2014;İpek, 2014;Vaziri et al, 2014;Ganji et al, 2015;Rastegarzade et al, (Fogarty, 2008;Hutton et al, 2009;Derry et al, 2012;Mamuk, 2017) Araştırma…”
Section: Doğum Ağrısının Yönetilmesiunclassified
See 1 more Smart Citation
“…Doğum ağrısının yönetimi için farmakolojik olmayan yöntemler hakkında gebeye bilgi vererek gebe karar verme sürecine dahil edilmelidir. Kadının dahil edilmediği bir süreç kadını bağımlı kılmakta ve sağlık personelini zorlamaktadır (Simkin & Bolding, 2004 tarih aralığında İngilizce "labor pain", "management of labor pain", non-pharmacological methods in management of labor pain" ve "midwife and labor pain" anahtar kelimeleri ile Türkçe "doğum ağrısı", "doğum ağrısının yönetimi", "doğum ağrısının yönetiminde farmakolojik olmayan yöntemler" ve "ebe ve doğum ağrısı" anahtar kelimeleri ile Google Akademik, Science Direct, Wiley Online Library, (Simkin & Bolding, 2004;Fogarty, 2008;Hutton et al, 2009;Derry et al, 2012;Hajiamini et al, 2012;Mollamahmutoğlu ve ark., 2012;Mortazavi et al, 2012;Allameh et al, 2015;Dong et al, 2015;Bolbol-Haghighi et al, 2016;Lakhan et al, 2016;Bonapace et al, 2018;Ranjbaran et al, 2017;Ghiasi et al, 2019;Suarez et al, 2019) Science Direct (Taavoni et al, 2016;Shahoei et al, 2017;Ünalmış 2017;Ali & Hamdia 2018) Cochrane Library (Lawrence et al, 2013;Madden et al, 2016) Researchgate (Askari et al, 2016;Regis et al, (Karami et al, 2007;Hashemi et al, 2012;Barbieri et al, 2013;Ghani, 2014;İpek, 2014;Vaziri et al, 2014;Ganji et al, 2015;Rastegarzade et al, (Fogarty, 2008;Hutton et al, 2009;Derry et al, 2012;Mamuk, 2017) Araştırma…”
Section: Doğum Ağrısının Yönetilmesiunclassified
“…Akupunktur/akupressür uygulaması, kapı kontrol teorisindeki kapı mekanizmalarından geçerek, ağrı uyaranın kapıdan geçmesini ve bilince ulaşmasını engellemektedir.Bilince ulaşan akupunktur/akupressür uygulaması ağrı geçişini engellediği için doğum ağrısını azaltmaktadır(Bonapace et al, 2018). Akupunktur/akupresür uygulanan gebelerle yapılan çalışmalarda; gebelerin doğum süresi ve ağrı skoru(Allameh, Tehrani & Ghasemi, 2015;Dong, Hu, Liang & Songying, 2015;Rastegarzade, Abedi, Valiani & Haghighi, 2015) daha düşük bulunmuştur.…”
unclassified
“…A registered, RCT of acupuncture and pethidine with 95 participants was performed at an Iranian hospital, from April to September, 2010 [25]. Randomization was by random number assignment.…”
Section: Acupuncture Versus Pethidinementioning
confidence: 99%
“…Analgesics were not administered to the 27 control participants [25]. A single dose of Pethidine 50 mg intramuscularly was received by 30 participants.…”
Section: Acupuncture Versus Pethidinementioning
confidence: 99%
“…Doses of up to 50 mg of intravenous (IV) or intramuscular (IM) pethidine do not cause relevant changes in maternal-fetal vitality. [6][7][8][9][10][11] Most studies found in the literature employ fixed doses of IV or IM pethidine ranging from 25 mg to 100 mg during labor. [12][13][14][15][16] After a search performed within the Capes, PubMed/Medline and BVS databases, from January 1st, 2000, to February 9th, 2016, we did not identify published research articles using doses of up to 50 mg of IV pethidine during labor in which the dosages were individualized according to the body mass of the parturients.…”
Section: Introductionmentioning
confidence: 99%